Pretrial innovations: supporting safety and case integrity - Vera Institute of Justice (My University, 2016)
The time between when an accused batterer is arrested and when the case is fully adjudicated can be especially dangerous for a victim of domestic violence. Most alleged offenders are released on bail, and many courts lack the ability to ensure that they meet the conditions of release. It is also a time when accused batterers are most likely to try to influence the outcome of the case, often using threats and sometimes violence. This publication examines several steps the Milwaukee County Courts took to ensure that pretrial orders are met and that the safety of the accuser is considered. It is part of the Judicial Oversight Demonstration Initiative's four-part series Enhancing Responses to Domestic Violence.